TEORI BIOLOGI TENTANG PERILAKU PENYALAHGUNAAN NARKOBA - Wahyuni Ismail (Jurnal Biotek, 2017)
This article aims to examine the theories of biologism related to risky behavior, especially the behavior of drug abuse from biologists are especially biologists of growth and brain development. The method used is literature research. Based on the results of literature research found there are 3 biological theories that can explain the validity of drug abuse behavior that is 1) genetic theory, 2) the theory of metabolic imbalance, and 3) brain biological theory. The implications of the study are expected to give the understanding that the biological state of the individual can influence the validity of drug abuse behavior.